Analisis Struktur Modal Optimal pada Perusahaan Makanan dan Minuman yang Terdaftar di LQ45 - Zilkha Febriana Kusuma Prambudi; Djoni Djatnika; Benny Barnas (Indonesian Journal of Economics and Management, 2021)
The research is about analyze optimal capital structure of food and beverage companies listed in LQ45, namely PT Indofood Sukses Makmur Tbk and PT Indofood CBP Sukses Makmur Tbk for the year 2015-2019. This research is using method descriptive quantitative with a secunder data from balance sheet and income statement PT Indofood Sukses Makmur Tbk and PT Indofood CBP Sukses Makmur Tbk for the year 2015-2019. In determining the optimal capital structure, the calculation of the cost of capital (CoC), the weighted average cost of capital (WACC) and firm value is used. The capital structure to be optimal if it has a low cost of capital so that it can increase the firm value. The results obtained from this research the two food and beverage companies listed in LQ45 can be said to have an optimal capital structure.